FUNGSI BADAN KEPEGAWAIAN DAERAH DALAM REKRUTMEN PEGAWAI DI LINGKUNGAN PEMERINTAH KOTA PEKANBARU - Ika Harmei Salina; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The success of the development is inseparable from the dedication of the apparatus of Government in carrying out its duties properly, because in practice it takes a clean government apparatus, authoritative and has high capabilities. The embodiment of a functioning State apparatus serving the public, professional, transparent, free of corruption, collusion and nepotism. To create a good government apparatus, then determined from the recruitment process. Badan Kepegawaian Daerah Pekanbaru is responsible for the conduct of the procurement officers. This is a function of the Badan Kepegawaian Daerah Pekanbaru. The process of recruitment is done in order to full fill the needs of civil servants in terms of the number of reliable and have the ability in their field. The purpose of the study is to know the functions of the Badan Kepegawaian Daerah Pekanbaru in a recruitment officer in the Government environment Pekanbaru and to know the factors that affect the function of the Agency's Staffing area in a recruitment officer in the Government environment Pekanbaru.The concept of the theory used is an organization that started from the guidelines for activities, a source of legitimacy, the standard implementation, a standard of rational motivation and basic organizing. This research uses qualitative research methods with the study of descriptive data. In data collection, the author uses interview techniques, observation, and documentation. With the use of key informants as a source of information and analysis of the data.The results of this research resulted in the conclusion that the role of the Agency in the implementation of Regional Staffing recruitment officers in the Government environment Pekanbaru has been running well the views of the activity guidelines are used, the standard execution of the recruitment, motivation and standards. While that factor – factors affect that affects Body step Kepegawain Area of the city of Pekanbaru in the recruitment of employees in the Government environment Pekanbaru is the infrastructure that has not been adequate as a computer and a human resources recruitment activities have not been adequate in terms of the number of recruitment methods and the control that uses a computer system.Keywords: Recruitment and implementation Functions